POLEMIK PILKADA 2020 DI MEDIA SOSIAL TWITTER - Bintang Samuel Silalahi; Ahmad Toni (Jurnal Komunikasi dan Budaya, 2022)
Regional head elections in Indonesia will be held at the end of 2020, to be precise, on December 9, 2020. Quoted from data taken from droneemprit.id, the 'PILKADA' TREND recorded around (175k) conversations on Twitter social media. The main purpose of this study is to examine the political communication that occurs on Twitter social media related to the pros and cons of the implementation of the 2020 Pilkada. Political communication that is built through Twitter social media, can shape public opinion and simultaneously mobilize massive political support, please note that Twitter has a very strong role to influence, and even shape the results of a campaign (Caplan, 2013, 12). The method used in this research is descriptive qualitative method. The data collection method in this study is library research. The results of this study show that the pros and cons of holding local elections are common, because through social media, twitter, political communication can occur massively.